Financial and managerial accounting: information for decisions - Wild, John J.; Larson, Kermit D.; Chiappetta, Barbara (Boston : McGrow-Hill / Irwin, 2005)
Business
Keywords: Accounting; Managerial accounting; Financial accounting; Cost accounting; Budgets and planning; Business transactions